Racionalnost moderne politike - Spruk, Jure (Teorija in praksa, 2022)
The article considers the question of rationality of modern politics, where the author opposes the image of politics in which the determining factor in politics is passions, not rationality. The main purpose is to show the rational dimension of the political that distinguishes modern political science. Since the political presupposes power relations between governors and the governed, the rational dimension of politics must be shown from both viewpoints. Whereas in the 16th century Machiavelli tried to introduce the rational dimension of politics to the prince, in the 17th century Hobbes attempted to find a grain of rationality in everyman. Both pioneers of modern political science confirm that what lies at the core of the political is rationality, which has to control passions in the sphere of political action.
Keywords: Hobbes, Thomas; Machiavelli, Niccolo; politična znanost; Politične vede; politika; razum